KAJIAN PERESEPAN RACIKAN STUDI RETROSPEKTIF PADA PASIEN PEDIATRI RSUD KABUPATEN TEGAL - Nisa, Silviatun (Journal Pharmactive, 2025)
The treatment of pediatric patients requires special attention because the organ systems of children are immature and continue to develop as they grow, concoction prescriptions are often found in pediatric patients, The demand for concoction prescriptions in pediatric patients arises from various specific needs of the patients such as administering a dose based on body weight, difficulty swallowing. Drug mixtures in concoction prescriptions increase the risk of drug incompatibility and interactions,Tthe research conducted was a cros sectional research with a retrospective approach. The data was 127 prescriptions concocted by outpatients in 2024, analyzed using Medscape stokley’s drug interactions, and literature study. The results showed that of 127 patients with male patients, 71 patients (55.9%) were female while the number of female patients was (44.1%). In the one-year period 52 cases (40.94) were found with dosage inaccuracies and stability problems in two cases (5.51%). From the analysis of 127 prescriptions, it was found that 66 prescriptions (52%) involved drug interactions with a moderate level of severity. The most common interactions occurred in combinations such as Catroptil + Furosemide + Lactosum, Tremenza + Salbutamol + Lactosum, and Phenytoin + Lactosum. Additionally, the potential for pharmaceutical problems was found to be an average of (46.46) Keywords: Drug interactions, pediatric, prescription concoctions.